2016
DOI: 10.1111/bph.13459
|View full text |Cite
|
Sign up to set email alerts
|

d‐Penicillamine modulates hydrogen sulfide (H2S) pathway through selective inhibition of cystathionine‐γ‐lyase

Abstract: BACKGROUND AND PURPOSEHydrogen sulfide (H 2 S) is a gasotransmitter produced from L-cysteine through the enzymatic action of cystathionine-γ-lyase (CSE) and/or cystathionine-β-synthase. D-Penicillamine is the D isomer of a dimethylated cysteine and has been used for the treatment of rheumatoid arthritis. As D-penicillamine is structurally very similar to cysteine, we have investigated whether D-penicillamine, as a cysteine analogue, has an effect on the H 2 S pathway. EXPERIMENTAL APPROACHWe tested the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 45 publications
0
34
2
Order By: Relevance
“…This inhibitory activity may account for the potential anti-inflammatory effect of H 2 S in inflammatory arthritis. Moreover, the NF-κB pathway was inhibited by H 2 S in different experimental studies [117,125]. Hence, the anti-inflammatory role is highly probably secondary to the inhibition of the transcription factor NF-κB, which has a key role in the pathogenesis of inflammatory arthritis as described above (see Figures 2 and 3) [126,127]; furthermore, it can induce the synthesis of the anti-inflammatory cytokine IL-10 [106].…”
Section: H 2 S and Arthritic Diseasesmentioning
confidence: 96%
See 1 more Smart Citation
“…This inhibitory activity may account for the potential anti-inflammatory effect of H 2 S in inflammatory arthritis. Moreover, the NF-κB pathway was inhibited by H 2 S in different experimental studies [117,125]. Hence, the anti-inflammatory role is highly probably secondary to the inhibition of the transcription factor NF-κB, which has a key role in the pathogenesis of inflammatory arthritis as described above (see Figures 2 and 3) [126,127]; furthermore, it can induce the synthesis of the anti-inflammatory cytokine IL-10 [106].…”
Section: H 2 S and Arthritic Diseasesmentioning
confidence: 96%
“…In addition, H 2 S concentration in the bloodstream was increased in patients with RA, and it was also associated with high numbers of circulating leukocytes [13]. As further support of a possible pathogenic role in inflammation, d-penicillamine, used in the past for the treatment of RA, resulted as a direct inhibitor of the synthesis of H 2 S and as a direct inhibitor of CSE activity [117]. In particular circumstances, the pro-inflammatory effect of H 2 S seems to be mediated by the induction of the expression of the intracellular adhesion molecule (ICAM)1, which may increase cell migration into the inflamed tissues [118].…”
Section: H 2 S and Arthritic Diseasesmentioning
confidence: 97%
“…Hence, our findings highlight the H 2 S-producing enzyme CSE as a potential therapeutic target to restrain TB disease. For example, D-Penicillamine (Cuprimine), which is commonly used to treat rheumatoid arthritis, targets CSE (36). H 2 S exerts a wide variety of biological pleiotropic functions because of its biphasic character.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the CSE precursor, L‐cysteine (1–10 mM), elicited a concentration‐dependent inhibition of the degranulation caused by FcεRI activation in RBL‐2H3 cells. The selective CSE inhibitor D‐Pen (1 mM)(Brancaleone et al , ) significantly antagonized the effect of 10 mM concentration of L‐cysteine (Figure B). The expression of CSE, in the presence of antigen and of increasing concentrations of L‐cysteine, did not differ from control values, indicating that the inhibitory effect of L‐cysteine was not due to a change in CSE expression (Figure C).…”
Section: Resultsmentioning
confidence: 89%
“…inhibitor D-Pen (1 mM) (Brancaleone et al, 2016) significantly antagonized the effect of 10 mM concentration of L-cysteine ( Figure 2B). The expression of CSE, in the presence of antigen and of increasing concentrations of L-cysteine, did not differ from control values, indicating that the inhibitory effect of Lcysteine was not due to a change in CSE expression ( Figure 2C).…”
Section: Endogenous H 2 S Inhibits Antigen-induced Degranulation In Rmentioning
confidence: 88%